Achieving improved workability and competitive high temperature shape memory performance by Nb addition to Ni-Ti-Hf alloys. (15th January 2021) - Lemke, J.N.; Gallino, F.; Cresci, M.; Coda, A.
Abstract: This work depicts how Nb addition to Ni-Ti-Hf alloys increases their ductility without significantly deviating functional performance due to the formation of eutectic constituents composed of soft β-Nb and B19' Ni-Ti-Hf matrix phase. Crucial for designing high performing Ni-Ti-Hf-Nb alloys is considering consequences of the low solubility of Nb in the matrix and the varying solubility of elements in β-Nb on the transformation temperatures. A case study on a drawn Ni-Ti-Hf-Nb wire demonstrates that improved mechanical properties and high transformation temperatures can be achieved by this approach, increasing the possibility for wire drawing of high temperature shape memory alloys. Graphical abstract: Image, graphical abstract